2014
DOI: 10.3109/09638288.2014.967415
|View full text |Cite
|
Sign up to set email alerts
|

Long-term community reintegration: concepts, outcomes and dilemmas in the case of a military service member with a spinal cord injury

Abstract: Jake's case challenges existing models of rehabilitation predominantly focused on physical capacity building. Study findings point to the need for rehabilitation to invest more resources in efforts to address the existential and social elements of long-term social reintegration. Implications for Rehabilitation Both the veteran with SCI and their meaningful support network face challenges socially reintegrating after injury and rehabilitation. Empowering clients to envision future possibilities in terms of fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…This showed the actual experiences of people with acquired disabilities, and focusing on only one experience might lead to a stereotypical image of them. The ambivalent meanings of disability were strongly related to family issues, disabilityrelated experiences, and age/generation normative experiences (Fritz, Lysack, Luborsky, & Messinger, 2015), where sociocultural norms regarding family, gender, and disability in Japan took an important role. The current participants did not passively accept these norms but actively challenged them.…”
Section: Resultsmentioning
confidence: 99%
“…This showed the actual experiences of people with acquired disabilities, and focusing on only one experience might lead to a stereotypical image of them. The ambivalent meanings of disability were strongly related to family issues, disabilityrelated experiences, and age/generation normative experiences (Fritz, Lysack, Luborsky, & Messinger, 2015), where sociocultural norms regarding family, gender, and disability in Japan took an important role. The current participants did not passively accept these norms but actively challenged them.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, social participation in such patients is severely restricted. 2) Although previous studies have reported that various kinds of devices and orthoses allow patients with high cervical SCI to improve their level of social participation, their involvement in society is still largely limited. 3,4) Nonetheless, several reports have shown that service dogs can assist with bodily functions, improve the psychological well-being of disabled people, and eventually enhance social participation.…”
Section: Introductionmentioning
confidence: 99%
“… 26 Many will also need timely interventions and preventive well-being programs (eg, weight control, stress reduction and exercise) in order to avoid secondary and tertiary conditions since individuals with disabilities are at a higher risk of medical complications. 27 , 28 It is also vital to address the existential and social needs of veterans 29 and provide additional resources and support to families and caregivers. 30 …”
Section: Introductionmentioning
confidence: 99%